Pendampingan Pemanfaatan Sosial Media YouTube dalam Pembelajaran IPS Mts Darul Huda Mayak - tesa nanda (https://ejournal.insuriponorogo.ac.id/, 2024)
This article aims to discuss the use of YouTube social media in social studies learning at MTs. Darul Huda Mayak Ponorogo, especially in supporting an effective and enjoyable learning process. This research is limited to evaluating the benefits, challenges and obstacles faced by teachers and students in using YouTube as a learning medium. The research methods used are observation, interviews and decumentation. Data was collected through interviews with teachers and direct observation of the learning process. The research results show that YouTube provides various benefits, including increasing student motivation, facilitating collaborative learning, and providing flexibility in study time. However, there are several significant challenges, such as limited supporting devices, unstable internet connections, difficulty finding relevant content, and managing learning time. Teachers also face obstacles in downloading videos and managing students' diverse attitudes during learning.